PENGARUH CITRA MEREK DAN PERLUASAN MEREK TERHADAP KEPUTUSAN PEMBELIAN KOPIKO WHITE COFFE - ERRIKAYASA ERVANDO, OSSYA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract : The aims of this research are to analyze and discuss the effect of brand image and brand extentionof Kopiko on customers purchase decission product Kopiko White Coffee . The type of this research is quantitative. The sampling technique that used was purposive sampling with sample size of 220 respondents. Data analysis techniques that used are validity test, reliability test and multiple linear regression analysis using PASW Statistics 18 software. Result of the research shows that there are linear relationship between independent variable and dependent variable, it means that citra merekand brand extention of Kopiko has positive effect on customers purchase decission on product Kopiko White Coffee (study on Economic FacultyState University of Surabaya) that is proven by positive sign at the regression formula. Keywords: brand image, brand extention, and purchase decission.